Migration between Africa and Europe (Springer International Publishing, 2018)
This volume examines migration between Africa and Europe, rather than just from Africa to Europe. Based on a unique socio-demographic survey carried out both in origin and destination countries (MAFE survey), it argues that return migration, circulation, and transnational practices are significant. Policy design must also take these factors into account. Comparing in a systematic way three flows of African migrants (from Democratic Republic of Congo, Ghana and Senegal), this study offers a new view on the patterns, determinants, and family and economic effects of migration. By comparing six European countries (Belgium, France, Italy, the Netherlands, Spain and the UK), it shows that the dynamics of migration differ greatly in new vs. old destination countries. Based on a statistical analysis of life histories, this study provides a dynamic view of migration that will help readers better understand current trends as well as future trajectories. It will appeal to researchers, academics, practitioners, and others interested in taking a deeper look in (im)migration issues.